Factors Influencing the Choice of Entrepreneurship Part of The University Graduates in Science and Management - Marouane, Saadia; Rhihil, Abdallah; Mouadni, Maha; El Bouzidi, Asmaa; El Ardi, Soumia (Archives of Business Research, 2023)
This article aims to study the entrepreneurial intention for two categories of students who differ in their disciplinary path. The objective is to understand how Moroccan students perceive the entrepreneurial processes. We based ourselves on the theory of planned behavior, where the intention to start, a business is supposed to depend on three variables (attitudes associated with the behavior, social norms and perceptions of behavioral control). The model is tested on 735 students in the process of obtaining their university degrees from management establishments and 315 students from science and technical establishments. The results generally confirm the explanatory model of the theory of planned behavior for science students, since the three variables have the impact on entrepreneurial intention and partially for management students. The study allows us to identify the types of professional expectations that most explain the attractive of students to launch in the entrepreneurial world and the competences for successful business creation. Perhaps we have "simplified" the process of building entrepreneurial intention, which is probably more complex and which certainly requires real exploration work in continuous in the field. This article represents a guide for the organizations responsible for supporting project leaders and a vector of economic and social development, allowing the realization of added value and participating in the fight against unemployment and informal work.